A DIFFERENTIATED APPROACH TO THE TREATMENT OF CAGA H. PYLORI - ASSOCIATED INFLAMMATORY DISEASES OF THE UPPER GASTROINTESTINAL TRACT WITH FOOD ALLERGY - I. Lozyuk (Bukovynian State Medical University, 2019)
Summary. According to world statistics, inflammatory deseases of the upper gastrointestinal tract (IDUGIT) occupy a leading place in the structure of gastroenterological diseases in children, the trigger factor for the development of which is H. pylori, the realization of which pathogenic effect on mucosa occurs in the presence of favorable conditions created in particular by food hyperreactivity. Recommendations for the diagnosis and treatment of patients with Helicobacter-associated IDUGIT are continually being improved, however, when combined with food allergy (FA), this problem has not yet been fully resolved, and there is much discussion. The aim of the study was to evaluate the effectiveness of complex treatment of IDUGIT in patients with cytotoxic strain CagA H. pylori and FA with the inclusion of an immuno-correcting agent. Material and methods. Detail clinical, paraclinical, and instrumental studies were performed to 44 children with CagA H.pylori-associated IDUGIT and FA, 7-18 years of age, before and in 4 weeks after treatment, and in the annual catamnesis. The effectiveness of complex treatment with the addition of protocol immunocorrective agent on the basis of the analysis of time of clinical reduction of the main gastroenterological syndromes and skin manifestations of FA, normalization of indicators of immunogram, endoscopic and morphological picture of stomach and duodenum mucosa, functional state of the stomach, achieving eradication of H.pylori. Discussion. With the inclusion in the treatment of immunocorrective agent in children with IDUGIT in combination with FA, a faster disappearance of the main gastroenterological syndromes of diseases, improvement of endoscopic (90.9%) and morphological (81.8%) picture, normalization of the functional state of the stomach was noted. %) when the eradication threshold was exceeded by 80,0%, skin manifestations of FA were reduced 3.2 times more often by reducing the SCORAD index to 18.92 p., normalization of immunological shifts was found 2.4 times more frequently. Conclusion. Children with IDUGIT associated with the cytotoxic strain of CagA H. pylori, in combination with FA, require complex treatment with the inclusion of an immuno-correcting agent, which will allow rapid clinical-paraclinic and endoscopic-morphological efficacy, 7 %, will reduce the risk of relapse by 2.33 times.